Fruitarian Diet and Blood Glucose Control in Type 1 Diabetes: A Case Report - Vetrani, Claudia; Bozzetto, Lutgarda; Della Pepa, Giuseppe; Rivellese, Angela Albarosa; Annuzzi, Giovanni (Frontiers in Nutrition, 2022)
Diet is a key determinant of blood glucose control in individuals with type 1 diabetes. Although dietary education is part of their clinical follow-up, many patients show a propensity to self-treatment adopting dietary changes -often extreme- that do not consider overall impact on health. Here, we describe the case of a type 1 diabetes patient who moved to a fruitarian diet for ideological beliefs. A 25-years-old man with type 1 diabetes on insulin pump and continuous glucose monitoring on optimal blood glucose control (HbA1c 6.5%, 44 mmol/mol; glucose time-in-range 70-180 mg/dl, TIR 90%; coefficient of variation, CV 36%) moved to a fruitarian diet for ideological beliefs. After 3 months on this diet, blood glucose control was still optimal (TIR 88%, CV 33%), while plasma triglycerides and liver enzymes were above normal values. After three more months, blood glucose control had worsened (TIR 72%, CV 37%), plasma triglyceride and liver enzymes were within normal values, and hyperkalemia was detected. In this case report, a strict fruitarian diet was associated with early negative changes in some biochemical parameters, also in presence of an optimal blood glucose control. Dietary counseling remains essential in the follow-up of patients with type 1 diabetes to ensure personalized medical nutrition therapy and monitor dietary changes that may affect health with no major impact on blood glucose control.